The acquisition of Spanish as a foreign language: a lexical-enactive approach (Signifiances (Signifying), 2024)
The purpose of this article is to demonstrate how the environment is responsible for the construction of the lexicon in the acquisition of a foreign language and, in particular, Spanish as FL. Our study focuses on the acquisition of Spanish by Italian learners. It takes into consideration the existence, for these learners, of a unique conceptual system, but with branches for the acquisition of a foreign language that arise, not so much from the conceptual system directly, but from the L1. We who are not native speakers can come into contact with our lexicon through the experience we have had with the L1. Whoever learns an L2, especially at an A1-A2 level, looks for expressions in his L1 to translate them into the L2 through their mental construction, while a native will extract the information directly, concretizing the experience of emotion without going beyond the L1: all this is regulated, at a neurophysiological level, by the prefrontal cortex that controls the lexicon. What we will try to argue in this article is the way in which a lexical-enactive approach in teaching Spanish as FL can be very useful when acquiring lexical competence in a foreign language.